Alignment analysis of Brainlab knee 3 navigation-guided total knee arthroplasty using the adjusted mechanical method - Yuqi, Pan; Jiang, Bowei; Li, Yige; Yu, Yuhao; Yunsu, Chen (Frontiers in Surgery, 2022)
Abstract Purpose: With the application of navigation technology in Total Knee Arthroplasty (TKA), TKA procedures have become various. Studies have shown that navigation can improve the alignment of patients' lower limbs. To verify this conclusion, we collected the clinical data from patients who underwent Brainlab knee 3 navigation guided TKA. Brainlab knee 3 is a completely new software that takes a different approach to address the current challenges of navigated TKA. During the procedure, we applied the AMA principle and took soft tissue balance as a priority. We aim to explore the patients’ lower limb alignment changes who underwent the Brainlab knee 3 navigation guided TKA using the AMA method. METHODS: Fifty consecutive patients who underwent total knee arthroplasty using the Brainlab knee3 knee navigation system from January to August 2021 by the same doctor (Yunsu Chen) in the Department of Joint Surgery of the Shanghai Sixth People's Hospital were included. HKAA, FTA, LDFA, and MPTA were measured on preoperative and postoperative full-length lower-limbs X-ray films or weight-bearing anterior and lateral knee radiographs for observational and descriptive study. The preoperative and postoperative knee alignment changes were analyzed through paired t-test or nonparametric Wilcoxon test using SPSS 25.0 software RESULTS: The mean preoperative HKAA was 169.8°; the postoperative HKAA was 175.7°. Using the two-sample paired t-test to analyze, a statistically significant difference exists. The mean preoperative FTA was 174.7°; postoperative 175.6°. Using the two-sample paired t-test to analyze, the difference was not statistically significant. The mean preoperative LDFA was 90.7°; the median of postoperative LDFA was 91.6°. Using the two-sample paired Wilcoxon test, the difference was not statistically significant. The mean preoperative MPTA was 83.5°; the median of postoperative MPTA was 89.3°. Using the two-sample paired Wilcoxon test, a statistically significant difference exists. CONCLUSION: In our study, AMA alignment was applied in Brainlab Knee3 computer navigation-assisted total knee arthroplasty. The femoral and tibial osteotomy angles were minimally adjusted according to soft tissue situations to reduce soft tissue release. We found AMA alignment provides good control of knee alignment in the coronal plane of the lower limbs, which is a reliable technique.